MODEL PEMBELAJARAN FAN-N-PICK (FNP) DALAM MENINGKATKAN KETERAMPILAN SOSIAL PADA PEMBELAJARAN IPS SISWA SEKOLAH DASAR - Seran, Eliana Yunitha; Relita, Dessy Triana; Marganingsih, Anna; Herlina, Maria (STKIP Persada Khatulistiwa Sintang, 2024)
This research is motivated by the phenomenon of elementary school students' low social skills and is influenced by internal and external factors. The focus of the study in this research is the use of the Fan-N-Pick learning model in improving students' social skills in social studies learning. This research aims to improve social skills after using the Fan-N-Pick learning model with elementary school students. The research method uses classroom action research, with the subjects of this research being class IV students at SDN 1 Keberak, totaling 24 students. Data collection tools use observation sheets, test sheets, questionnaires and document sheets with data analysis techniques using interactive analysis form. The results of the research show that using the Fan-N-Pick model can improve students' social skills and learning outcomes in theme 7 subtheme 1 with a very good category, improving students' social skills using the Fan-N-Pick model in cycle I, the observation score obtained was 64. 50% and cycle II 85.67%, resulting in an increase of 21.17%. Meanwhile, students' responses to using the Fan-N-Pick model were also very good and received positive responses based on interview results. It was concluded that the Fan-N-Pick learning model can improve elementary school students' social skills in social studies learning.